The effect of exercise in the development of the proposed strike force arm accurately strike the ground in front of tennis - Jassim, talab (Journal of Physical Education, 2010)
The objective of research was to determine the effect of exercise proposed in the development of arm strength strike and accurately in front ground strike in tennis game, and accelerate the achievement of tangible development through manner to design exercise consistent, researcher suggested that there is a positive influence in the development of strong arm, s accurately in front ground strike in tennis game tricking the front accurately strike the ground in a game of tennis by adopting proposed training exercise, the researcher used the experimental approach, the experimental group included 10 students from the students of the third stage physical education college - University of Baghdad . The researcher concluded : that the proposed exercises led to noticeably development arm strength and accuracy in front ground strike in tennis game in search sample . And recommendations of the study : the adoption exercises are important in improving the level of performance, when the arm is the development of accuracy, as well as reducing the speed of movements in the training .